The Role and Legal Aspects of Infaq, Sadaqah, and Waqf in Realizing Economic Equality and People's Welfare - Moh. Hamzah (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2024)
Infaq, sadaqah, and waqf are crucial instruments in promoting and realizing an economy characterized by justice and widespread community welfare. However, there are several challenges in fulfilling their significant roles, including the lack of awareness and understanding among the public regarding the concepts of Islamic philanthropy. Therefore, this research focuses on the contribution of infaq in achieving community welfare and social solidarity, the tangible expression of social concern through sadaqah in Islam, and the regulation of waqf in Indonesia. This study employs a qualitative research approach, utilizing descriptive analytical methods. The findings of this research highlight that infaq has a strong relevance to its contributions to society. By optimally implementing the concept of infaq, it can provide substantial contributions in several crucial aspects of community life. Sadaqah, as a tangible expression of social concern in Islam, has significantly contributed to fostering mutual care and has implications for the equitable distribution of wealth among the community. Furthermore, the optimization of waqf implementation in Indonesia is realized based on Law No. 41 of 2004 on Waqf, the Compilation of Islamic Law Articles 215 to 229, and Government Regulation No. 28 of 1977 on Endowments.